Environmental assessment of urine, black and grey water separation for resource recovery in a new district compared to centralized wastewater resources recovery plant. (10th June 2021) - Besson, Mathilde; Berger, Sylvaine; Tiruta-barna, Ligia; Paul, Etienne; Spérandio, Mathieu
Abstract: Current trends show that wastewater treatment plants (WWTPs) will intend to shift towards water resources recovery facility (WRRF), however nutrients recovery in WRRF is limited by the need of highly concentrated stream for the process. Source separation can help to increase this potential, but assessment is necessary to evaluate the whole system at district scale. In this study three scenarios based respectively on urine diversion, blackwater and greywater separation were compared to the conventional end-of-pipe strategy with adjunction of treatment at the centralized WRRF for producing renewable fertilizers and energy. Life cycle assessment was used to compare environmental impacts. The study was performed to represent the implementation of a new district in an urban context. Treatments have been chosen among the best technologies available for resource recovery. Results show that for maximizing nutrients recovery and limiting the greenhouse gas emissions, urine and blackwater separation are better scenarios than conventional mixing option and centralized WRRF. Indeed it allows to mitigate by at least 60% the nitrous oxide (N2 O) emissions and to avoid nitrogen fertilizer production which emits large amount of greenhouse gases (8.6 kg CO2-Eq/kgN). Urine source separation is particularly beneficial by recovering nitrogen at a low environmental footprint: impact on climate change decreases by 45% compared to the Reference. The separation of blackwater treated at decentralized scale shows a decrease of 34% of impact on climate change compared to Reference, thus a little worse than Urine due to a higher external energy demand at decentralized scale for nitrogen recovery. Phosphorus can be recovered in all the source separation system without additional climate change impact. If the priority is given at water reclamation the treatment of blackwater and greywater separately is a valuable option. However energy balance and greenhouse gases emissions analysis do not support this scenario if highly energy consuming technology is used for greywater treatment (more than 0.56 kWh/m 3 treated). It would become acceptable in case of decarbonized energy or if tap water production is a high greenhouse gases emitter. Graphical abstract: Image 1 Highlights: Source separation scenarios were compared to centralized resource recovery facility. Urine and black water separation reduce by 45% and 34% greenhouse gas emissions. Nitrogen recovery can lead to neutral GHG emissions plant. Greywater reuse increases climate change impact due to high energy consumption for MBR.